Heat dissipation and inter-relationship between physical properties of moulding sand. (2021) - Vinothraj, D.; Ragavanantham, S.; Saravanakumar, M.; Vivekananthan, M.; Sivagnanamani, G.S.
Abstract: The heat dissipation across the moulding sand decides the rate of solidification of castings. For defect free castings, the cooling rate has to be at a preset level. The coarse, medium and fine sand moulds, the properties of the moulding sand like permeability, green compression strength, flowability, compactibility, and mould hardness influence the heat dissipation rate across the mould. An experimental investigation is carried out to understand the influence of these parameters over heat dissipation rate. The grain coarse and fine are found to a major influencing parameter. Analysis of results gives solidification time of Aluminum casting in coarse, medium & fine sand moulding and the inter relationship between physical properties and solidification rate.